Informação de custos na Unidade Saúde Escola da universidade Federal de São Carlos (USE/UFSCar): um mapeamento baseado nos sistemas e controles existentes - Ataide, Vilma Martins de (2018)
In view of legal requirements that aim at improving quality of cost information by all federal departments and the complexity of calculating costs in public institutions, the present study investigated process of structuring cost information in the School Health Unit (SHU) of Federal University of São Carlos, the costing investigation process and the utilization, or not, of information systems in the scope of the university. The research is characterized by the integration of quantitative and qualitative information, in the form of a case study - according to the objectives it is classified as descriptive and exploratory. The multiple sources of evidence used for data collection enabled the identification and mapping of items consumed directly and indirectly by SHU, and according to the cost structure by absorption, the general unit costs were calculated. Using database information’s, the full financial cost of SHU was calculated and the representativity of each item and its group was identified, evidencing the participation of information systems used by the institution in the construction of cost information. It was found that the existing costs in the SHU are predominantly permanent, where the prevalence of certain groups of expenses was verified. The cost of the expense groups, salaries, personnel benefits and social taxes, represents almost 80% of the total cost in SHU. Permanent costs bring limitations to managers at any level of decision, because oftenly, they cannot be avoided and because they are costs related to legal obligations, as is the case of costs with effective servers. Regarding the information systems in the calculation of cost, it was verified that the generation of cost information for the object in study was only possible with the predominant use of manual control, once that most of informations was provided by Excel spreadsheets, which directly affects the reliability and quality of informations. Existing data in the information systems used by the University require adaptations and systemic integrations to then, offer cost information at the departmental level.